Perioperative hormone level changes and their clinical implications in patients with pituitary adenoma: a retrospective study of 428 cases at a single center - Zhao, Min; Li, Kai; Niu, Hongchuan; Zhao, Yuanli; Lu, Changyu (Frontiers in Endocrinology, 2023)
Objective: This study employs case data analysis to elucidate alterations in hormone levels pre and post-surgery among patients with pituitary adenoma. Moreover, it investigates the influence of various associated factors on endocrine function.A retrospective analysis was conducted on clinical data from 428 patients who underwent surgical treatment within a short period at a single center. Statistical methods were employed to examine detailed hormone level fluctuations before and after surgery in patients with pituitary adenoma, along with their interrelations with different factors.Between January 2016 and October 2022, a total of 428 consecutive patients with pituitary adenoma underwent surgical treatment, 232 males and 196 females, with an average age of 45.91 years (range: 16-84). Univariate analysis indicated that females exhibited a higher susceptibility to preoperative endocrine dysfunction (p < 0.05). Conversely, males, patients with larger tumor, and older patients were more prone to preoperative pituitary insufficiency. Postoperatively, the most substantial remission rate occurred in prolactin (77.4%), followed by growth hormone (GH) (71.8%) and cortisol (4/6). The highest recovery rate in functions was observed in growth hormone secretion function (80%), followed by pituitary-adrenal axis hormone secretion function (56.3%) and pituitary-thyroid axis hormone secretion function (47.5%). The most noteworthy incidence of newly developed postoperative endocrine deficiencies was found in the pituitary-adrenal axis (31.8%), while the occurrence rates of deficiencies in other axes were relatively low. The elevated postoperative remission rate of growth hormone correlated with a higher resection rate and lower preoperative growth hormone levels. Additionally, lower preoperative prolactin levels corresponded to a higher remission rate of prolactin postoperatively. Furthermore, the restoration of postoperative thyroid hormone secretion function was associated with higher preoperative free thyroxine levels. Reduced postoperative cortisol secretion function was linked to multiple surgeries and an extended interval between hormone retesting and surgery.Surgical intervention effectively ameliorates endocrine disorders in pituitary adenoma patients, thereby mitigating symptoms and enhancing their quality of life. Preoperative management of growth hormone and prolactin levels facilitates an increased remission rate of these hormones post pituitary adenoma surgery. Patients displaying preoperative thyroid hormone secretion dysfunction should be considered for active supplementation therapy. Whenever feasible, complete tumor resection is recommended.